2015
DOI: 10.1097/ico.0000000000000535
|View full text |Cite
|
Sign up to set email alerts
|

Small-Fiber Neuropathy Is Associated With Corneal Nerve and Dendritic Cell Alterations

Abstract: CCM provides parameters that reliably indicate injury to sensory afferents of the trigeminal nerve in patients with SFN. Our data suggest that CCM may serve both as a noninvasive diagnostic test and as a surrogate marker in SFN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
2
30
1
1
Order By: Relevance
“…Applying CCM, lower CNFD was found in previous studies comparing SFN patients with healthy controls . Further findings in SFN patients were shorter CNFL, less nerve fiber branching, and higher corneal nerve tortuosity than in healthy controls. LC counts did not differ between SFN patients and controls .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Applying CCM, lower CNFD was found in previous studies comparing SFN patients with healthy controls . Further findings in SFN patients were shorter CNFL, less nerve fiber branching, and higher corneal nerve tortuosity than in healthy controls. LC counts did not differ between SFN patients and controls .…”
Section: Discussionmentioning
confidence: 61%
“…Further findings in SFN patients were shorter CNFL, less nerve fiber branching, and higher corneal nerve tortuosity than in healthy controls. LC counts did not differ between SFN patients and controls . We showed lower CNFL and corneal nerve fiber branching in SFN patients than in controls, whereas CNFD did not differ.…”
Section: Discussionmentioning
confidence: 82%
“…Even though a formal cost-effectiveness analysis was beyond the scope of the present work, it is conceivable that this substantial minimization of examination time may enable more widespread screening for CAN. Interestingly, the present attempt at shortening the examination time is in the same context as the suggested simplification of nerve conduction study by the sural sensory/radial motor amplitude ratio [24] and some innovations in corneal confocal microscopy [25][26][27]. Nonetheless, it should by no means be suggested that a simple index like the 30:15 ratio, or a combination of the 30:15 ratio with the VR, the E/I/VR, and the rise in diastolic blood pressure, could currently replace the validated 5 Ewing tests.…”
Section: Discussionmentioning
confidence: 99%
“…This non-invasive technique uses a combination of corneal nerve fiber length, nerve branch density, and nerve fiber density to evaluate the corneal nerve plexus 175176. It has been shown to detect early small nerve fiber damage in many disorders 175177178179180181182. This technique has advantages over skin biopsy as it is rapid and non-invasive, but it is not yet widely available.…”
Section: Diagnostic Approachmentioning
confidence: 99%